Design of Educational Game-Based Learning Media "Si Advent" on the Material of Growth and Development of Living Things in Grade III - Saputra, Muhammad Rizky; Sufa, Feri Faila; Sutikno, Arif (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2023)
This study aims to determine the feasibility of educational game-based learning media design as a science learning media on the material ofgrowth and development of living things at SD N Tegalayu 96 Surakarta. Researchers use the Research and Development (R&D) methodwith the Dick and Carey research procedure model, namely the ADDIE model which has been simplified. Data collection uses interviews,questionnaires, and documentation methods and is combined with a Blackbox Testing system and validation of product feasibility byExpert Judgement and learner responses which are analysed using a Likert Scale. The results of this study also show that educationalgame-based learning media according to the assessment by material experts get a feasibility percentage of 94.54% with a very feasiblecategory, by media experts get a feasibility percentage of 81.6% with a very feasible category, by educators get a feasibility percentage of96.15% with a very feasible category, as well as an assessment response by students of 88.75% with a very feasible category.Keywords: Design, Learning Media, Educational Game, Science, R&D.